Activated biomass carbon made from bamboo as electrode material for supercapacitors. (June 2018) - Zhang, Guoxiong; Chen, Yuemei; Chen, Yigang; Guo, Haibo
Graphical abstract: Highlights: Activated biomass carbon (ABC) produced from bamboo was prepared by carbonization and KOH activation. The BET and morphology of the ABC have a strong dependence on the activation temperature. High specific capacitance along with durability is achieved. Activated biomass carbon can serve as efficient electrode material for energy storage. Abstract: Activated biomass carbons (ABC) produced from bamboo by carbonization and activation have high specific surface areas and mesoporous structures. The specific surface area, total pore volume, and average pore size of the activated biomass carbon are controlled by adjusting the activation temperature from 700 to 1000 °C. The carbon materials activated at 900 °C have an optimal mesoporous structure with a high specific surface area (2221.1 m 2  g −1 ), the highest capacitance (293 F g −1 at 0.5 A g −1 in 3 M KOH aqueous electrolyte) and excellent rate capability (193.8 F g −1 at 20 A g −1 ). Symmetric supercapacitors made of the optimal electrodes exhibit a high energy density of 10.9 Wh kg −1 (18.2 Wh L −1 ) at a power density of 63 W kg −1 (105 W L −1 ) and outstanding capacitance retention of 91.8% over 10, 000 cycles. The high electrochemical performance of the mesoporous ABCs show that they are highly promising for energy-storage applications with further optimization.